Book Receipts (2014)
Dr. Dídima Rico has given me this interesting book that is a kind of interview by the communicator Angel Beccassino to the jurist and political scientist Alex Vernot. There are many topics such as political and economic power, corruption, machismo, the legalization of drugs, the internet, prostitution and water, among others. Starting from the fact that the current system is unfair, it raises a "social capitalism" that closes the gap between rich and poor. It proposes solidarity, democratize knowledge and use common sense to unravel the functioning of things, the title of the work. It tells us that absolutes do not exist.